Formative processes of actions and reflections in the continuing education of the National Pact for Literacy at the Right Age Program in a municipality in the Northeastern region of Rio Grande do Sul (Práxis Educativa, 2020)
This article aims to understand the actions and impacts of the National Pact for Literacy in the Right Age Program in a municipality in the Northeastern region of Rio Grande do Sul, Brazil, and its alternatives to achieve goals of the National Education Plan, concomitantly to economic and social advances.  Throughout the Program, it was possible to put into practice methodological experiences that strengthened the continuing education for teachers capable of teaching from a critical perspective of Education. In the context of the research, a participative management was found, which interconnects government programs with critical proposals for the training of teachers in the Municipal Network, in a permanent and continuous action that starts from the assumption of the dialectic critical theory that encompasses its construction in the very praxis of professional action, appropriated from the reflection of teachers on their own teaching work performance at school and in permanent continuous training.Keywords: Continuing teacher Education. National Pact for Literacy in the Right Age. Public policies.